Breaking Up Communication Barriers: Identifying and Overcoming Verbal Communication Barriers in the Completion of Final Projects for Communication Science Students at the State Islamic University of North Sumatra - Siregar, Muhammad Hafiz; Tanjung, Muaz (Lafadz Jaya Publisher, 2024)
This study aims to explore strategies and techniques to overcome verbal communication barriers in an academic context, particularly between lecturers and students during the completion of final projects at the State Islamic University of North Sumatra (UIN-SU). Using interactive communication theory and uncertainty reduction theory, this research provides a framework for understanding and addressing these barriers. The research method employed is a qualitative approach with data collection techniques including in-depth interviews, direct observation, and related document studies. Data were analyzed using content analysis to identify patterns and trends in verbal communication. Triangulation, peer debriefing, and external checks were used to ensure data validity. The research results indicate that the communication model implemented by lecturers greatly influences the effectiveness of guidance and the quality of students' final projects. Communication barriers are often caused by misunderstandings in written communication and differences in expectations. Proposed solutions include effective communication training for lecturers, the use of written communication guidelines, and regular group and individual guidance sessions. The integration of communication technology such as e-learning platforms and online collaboration tools is also suggested to enhance the communication process. By understanding the dynamics of verbal communication and overcoming existing barriers, this research aims to improve the quality of academic guidance and student outcomes, as well as prepare them for communication challenges in the professional world. This study is relevant not only in the academic context but also has broad practical implications.